Laser Shocking Nano-Crystallization and High-Temperature Modification Technology - Ren, Xudong (Springer Berlin Heidelberg : Imprint: Springer, 2015)
The aim of this book is to present foundational research on the nano-crystallization, high-temperature modification, micro-structure evolution, and plastic deformation induced by laser shock processing. In this regard, the focus is on heat-resistant steel, aluminum alloy, Ti alloys and Ni-based alloys, offering valuable scientific insights into the industrial applications of laser shock processing (LSP) technology. The book addresses various topics, i.e., the formation mechanism and productivity improvement of nano-crystalline diamond by laser processing, the surface integrity and fatigue lives of heat-resistant steels, Ti alloys and Ni-based alloys after LSP with different processing parameters, tensile properties and fractural morphology after LSP at different temperatures, strain-rates and grain refinement mechanisms based on the micro-structure evolution. Moreover, the effect of heating temperature and exposure time on stress thermal relaxation and the influence of compressive stress on the stress intensity factor of hole-edge cracks by high strain rate laser shock processing are also analyzed. A new type of statistical data model to describe the fatigue cracking growth with limited data is proposed based on the consideration of the effects of fracture growth on the reliability and confidence level. This book is intended for researchers, engineers and postgraduates in the fields of nanotechnology and micro-engineering who are interested in the partial or overall strengthening of materials, especially those with a focus on surface integrity and fatigue life.